2013
DOI: 10.1063/1.4803479
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on structural, vibrational properties, and quasiparticle band structure of solid nitromethane

Abstract: We report a detailed theoretical study of the structural, vibrational, and optical properties of solid nitromethane using first principles density functional calculations. The ground state properties were calculated using a plane wave pseudopotential code with either the local density approximation (LDA), the generalized gradient approximation (GGA), or with a correction to include van der Waals interactions. Our calculated equilibrium lattice parameters and volume using a dispersion correction are found to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 55 publications
4
26
0
2
Order By: Relevance
“…There have been promising attempts made to fix this shortcoming, and considerable benchmarking studies are available with advanced methods for noble gas solids, layered, sparse and molecular crystals. [22][23][24][25][26][27][28][29][30][31][32] In the case of energetic materials, Sorescu et al 33 35 From our previous studies on nitromethane and FOX-7 solids, 36,37 we also found good agreement using Grimme and TS methods. However, it is observed that although the mentioned dispersion corrected methods overcomes most of the difficulty in reproducing ground state volumes, the relative errors still show a mean absolute deviation of about 3 %.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…There have been promising attempts made to fix this shortcoming, and considerable benchmarking studies are available with advanced methods for noble gas solids, layered, sparse and molecular crystals. [22][23][24][25][26][27][28][29][30][31][32] In the case of energetic materials, Sorescu et al 33 35 From our previous studies on nitromethane and FOX-7 solids, 36,37 we also found good agreement using Grimme and TS methods. However, it is observed that although the mentioned dispersion corrected methods overcomes most of the difficulty in reproducing ground state volumes, the relative errors still show a mean absolute deviation of about 3 %.…”
Section: Introductionsupporting
confidence: 57%
“…43,44 But the well known disagreement of the computed band gap using standard DFT functionals leads to an inaccurate estimation of the properties related to the band gap either in molecular or solid systems. However from our previous studies on some energetic materials (solid nitromethane, FOX-7, cynauric triazide) 36,37,45 and another theoretical study on TATB by Fedorov et al, 46 it is known that the GW approximation [47][48][49][50][51][52] can overcome this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Since MNO 3 nitrates contain molecular complexes (nitrate anions, NH 4 cations), it is important to take into consideration the weak intermolecular Van der Waals interactions. DFT can predict the properties of the energetic materials that are in close agreement with experiments provided the exchange-correlation functionals are corrected to describe the weak intermolecular interactions [7,[42][43][44][45][46][47][48]. Thus, in comparison with to the LDA and GGA [49] results , G. Vaitheeswaran et al [7] found that the crystal structure of alkali-metal nitrates is well described by the dispersion-corrected functional DFT-D [50].…”
Section: Introductionmentioning
confidence: 72%
“…Следовательно, знание структурных Поскольку перхлораты содержат молекулярные ком-плексы (перхлорат-анионы, NH 4 -катионы), важным яв-ляется учет слабого межмолекулярного взаимодействия Ван-Дер-Ваальса. Для этого обменно-корреляционный функционал должен быть скорректирован для описа-ния слабых межмолекулярных взаимодействий [28][29][30][31][32][33][34][35]. Так, в [28][29][30] установлено, что кристаллическая струк-тура хлората калия и нитратов щелочных металлов описывается таким скорректированным функционалом DFT-D [36] значительно лучше по сравнению с LDA и GGA [37].…”
Section: Introductionunclassified